Fluorescence-Based Protein Footprinting Using Histidine-Tagged Protein. (January 1998) - Rajendrakumar, G.V.; Adhya, Sankar
We describe a procedure for protein footprinting to identify the region(s) of a protein that interacts with a ligand. The method utilized the affinity of a stretch of histidine residues cloned into the protein to metalchelated resin. After limited protease digestion, the histidine-tagged end fragments were separated by the resin and labeled with a fluorescein derivative. Resolving the labeled digestion products on a denaturing polyacrylamide gel and visualizing the peptides using a FluorImager™ provided a way to identify the protease target sites that were protected from digestion because of interaction with DNA. The protection experiments would be applicable not only to detect direct contact sites but also sites allosterically altered by ligand binding.